Pengaruh Model Pembelajaran Collaborative Learning terhadap Motivasi Belajar PAK Siswa Kelas VII SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Asrita Anggina Sinaga; Frainskoy Rio Naibaho; Rawatri Sitanggang; Senida Harefa; Maria Widiastuti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to determine the differences in student learning motivation in PAK learning before and after it is taught using the Collaborative Learning learning model for class VII students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The research hypothesis is: